2020
DOI: 10.1111/jir.12722
|View full text |Cite
|
Sign up to set email alerts
|

An observational cohort study of numbers and causes of preventable general hospital admissions in people with and without intellectual disabilities in England

Abstract: Background Hospital admissions for preventable reasons [ambulatory care sensitive (ACS) conditions] can indicate gaps in access to or quality of primary care. This paper seeks to document the numbers and causes of these admissions in England for people with intellectual disabilities (ID) compared with those without.Methods Observational cohort study of number and duration of emergency admitted patient episodes for ACS conditions, overall and by cause, using the Clinical Practice Research Datalink GOLD primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…In the first Australian study of potentially preventable hospitalisations of people with intellectual disability, we found that age‐standardised rates were higher than for the general NSW population, without clear patterns of change in differences during 2001‒2015. Our findings are in line with findings from Canada, the United States of America, and the United Kingdom that rates of potentially preventable hospitalisation are higher for people with intellectual disability 8-11 . We found that rates were particularly high for hospitalisations for acute conditions, for which overall rates were five to eight times as high for people with intellectual disability as for the general population; the rates for admissions with vaccine‐preventable conditions were about three times as high.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the first Australian study of potentially preventable hospitalisations of people with intellectual disability, we found that age‐standardised rates were higher than for the general NSW population, without clear patterns of change in differences during 2001‒2015. Our findings are in line with findings from Canada, the United States of America, and the United Kingdom that rates of potentially preventable hospitalisation are higher for people with intellectual disability 8-11 . We found that rates were particularly high for hospitalisations for acute conditions, for which overall rates were five to eight times as high for people with intellectual disability as for the general population; the rates for admissions with vaccine‐preventable conditions were about three times as high.…”
Section: Discussionsupporting
confidence: 90%
“…One marker of poor access to appropriate primary and community‐based health care is the higher rate of potentially preventable hospitalisations for people with intellectual disability than for people without intellectual disability, as reported overseas 8-11 . In Australia, potentially preventable hospitalisations are a performance indicator of health care accessibility and effectiveness; twenty‐two ambulatory care‐sensitive conditions are encompassed by this indicator, including vaccine‐preventable, acute, and chronic conditions 12 .…”
mentioning
confidence: 99%
“…Standard psychosocial interventions for the general population are described as techniques, which target biological, behavioural, cognitive, emotional, interpersonal, social, or environmental factors can improve a person's health, function, and well‐being (England et al, 2015). Psychosocial interventions with adults who have an intellectual disability and mental ill health is an area in which there is limited research particularly internationally, even though factors which psychosocial interventions target are beneficial (Glover et al, 2020). This review underlines the lack of provision particularly with people who have varying levels of ability.…”
Section: Discussionmentioning
confidence: 99%
“…However, the challenges inherent in examining healthcare utilisation for children with ID necessitate the use of such data when hospital administrative data is unsuitable due to poor coding and a lack of diagnosis for children with ID (Emerson and Hatton 2013). Moreover, the clinical reasons and degree of the severity of illness for use of health services was not reported, which limited our ability to identify disparities in reasons for use and critically, if children with ID have a greater risk of avoidable hospitalisation for instance, ambulatory care sensitive conditions (Glover et al 2020) and/or differences in attendance for physical or mental health illness. Finally, due to the small sample sizes available, we were unable to examine disparities across categories of ID to determine whether those with severe and profound disability are at greater risk than those with mild or moderate disability.…”
Section: Strengths and Limitationsmentioning
confidence: 99%